RESULTS OF BACTERIOLOGICAL MONITORING OF URINARY TRACT INFECTIONS IN CHILDREN OF ZAPORIZHZHIA REGION IN 2023 - Lezhenko, Hennadii; Pashkova, Olena; Samoylyk, Kateryna; Petrashyna, Olena (Eastern Ukrainian Medical Journal, 2024)
The aim of the study. To investigate the structure of pathogens of acute urinary tract infections in children of Zaporizhzhia region in 2023 and their sensitivity to antibacterial agents.Materials and methods. The analysis of the structure of pathogens in acute urinary tract infections and the determination of their sensitivity to antibiotics based on the results of bacteriological urine cultures of 322 children with acute urinary tract infections treated at the Zaporizhzhia Regional Children's Hospital in 2023 was performed. For each isolate, the multidrug resistance index was calculated, which allowed to judge the relative integral resistance of the isolated microorganisms to antibacterial drugs.Results. It was established that the most common cause of urinary tract infections in children were gram-negative microorganisms (61.0%), including Escherichia coli (37.4%) and Klebsiella pneumoniae (10.8%) which were most often verified. Gram-positive bacteria were identified in 38.5% of patients, among which the Enterococcus bacteria (29.2%) predominated. High resistance of Escherichia coli to amoxicillin/clavulanate (31.5%), ciprofloxacin (30.1%), cefepime (20.1%), and ceftazidine (20.5%) was detected, including 29 (39.7%) multidrug-resistant isolates of Escherichia coli. The highest resistance of Klebsiella pneumoniae was found to amoxicillin/clavulanate (76.2%), cefepime (33.3%), ceftazidine (33.3%), ciprofloxacin (42.8%), and phosphamycin (28.6%). Multidrug resistance was shown by 76.2% of Klebsiella pneumoniae isolates. The highest susceptibility of Enterococcus bacteria was found to ampicillin (98.2%), linezolid (98.2%), vancomycin (100%), nitrofurantoin (100%), and tigecycline (100%). In no case microorganisms showed complete sensitivity to imipenem, and 17.9% of Enterococcus isolates were resistant to this antibiotic.Conclusions: At the present stage, the dominance of gram-negative microflora among the pathogens of urinary system infections in children remains, among which Escherichia coli (37.4%) continues to be the leading pathogen. The growing role of Enterococcus faecalis (29.2%) as an etiologic factor of urinary tract infections in children was noted, which should be taken into account during the empirical use of antibiotics, especially if there is no effect within the first two days after the start of therapy.